Neutrophil calprotectin identifies severe pulmonary disease in COVID‐19. Issue 1 (1st September 2020) - Shi, Hui; Zuo, Yu; Yalavarthi, Srilakshmi; Gockman, Kelsey; Zuo, Melanie; Madison, Jacqueline A.; Blair, Christopher; Woodward, Wrenn; Lezak, Sean P.; Lugogo, Njira L.; Woods, Robert J.; Lood, Christian; et al.
Abstract: Severe cases of coronavirus disease 2019 (COVID‐19) are regularly complicated by respiratory failure. Although it has been suggested that elevated levels of blood neutrophils associate with worsening oxygenation in COVID‐19, it is unknown whether neutrophils are drivers of the thrombo‐inflammatory storm or simple bystanders. To better understand the potential role of neutrophils in COVID‐19, we measured levels of the neutrophil activation marker S100A8/A9 (calprotectin) in hospitalized patients and determined its relationship to severity of illness and respiratory status. Patients with COVID‐19 ( n = 172) had markedly elevated levels of calprotectin in their blood. Calprotectin tracked with other acute phase reactants including C‐reactive protein, ferritin, lactate dehydrogenase, and absolute neutrophil count, but was superior in identifying patients requiring mechanical ventilation. In longitudinal samples, calprotectin rose as oxygenation worsened. When tested on day 1 or 2 of hospitalization ( n = 94 patients), calprotectin levels were significantly higher in patients who progressed to severe COVID‐19 requiring mechanical ventilation (8039 ± 7031 ng/ml, n = 32) as compared to those who remained free of intubation (3365 ± 3146, P < 0.0001). In summary, serum calprotectin levels track closely with current and future COVID‐19 severity, implicating neutrophils as potential perpetuators of inflammation and respiratory compromise in COVID‐19. Graphical Abstract: Serum calprotectin levels track closely with current and future COVID‐19 severity, potentially implicating neutrophils as active perpetuators of inflammation and respiratory compromise in COVID‐19.